Design and optimization of a medium flow differential mobility analyzer (MF-DMA) for classification of high-density particles. Issue 10 (3rd October 2019) - Rosenberger, T.; Kiesler, D.; Hontañón, E.; Fuentes, D.; Ramiro, E.; Kruis, F. E.
Abstract: A new design of a Differential Mobility Analyzer (DMA) was tested with medium aerosol flow rates ranging from 1.5 to 10 slm and high-density particles. The vacuum-tight construction makes it possible to classify pure metal nanoparticles from production processes. The selectable electrical mobility range is comparable to the TSI Long and Nano DMA and covers the full nanometer scale from 15–600 nm. The Medium Flow-DMA (MF-DMA) is characterized by its transfer function, which was determined by a tandem DMA setup using a SMPS with Long DMA downstream. Silver nanoparticles with a density of 10.49 g cm −3 were used to demonstrate the size-selecting performance of high-density particles. The transfer function was calculated for aerosol to sheath gas flow ratios of 1/10, 1/5, and 1/3 directly from the SMPS data by a new method using modeling approach and comparison to the theory. Sufficiently high resolution was reached by increasing the SMPS scan time of the classified size distribution to 300 s. During the investigation, a broadened transfer function could be attributed to an inhomogeneous flow field resulting from the aerosol inlet design. The aerosol inlet of the MF-DMA was optimized by the number of inlet drillings and the opening of the inlet slit to achieve a more homogeneous flow field. CFD simulations of the MF-DMA also confirmed this. The modification improved the transfer function especially for medium aerosol flow rates above 5 slm. Copyright © 2019 American Association for Aerosol Research